Real-time monitoring system for local storage and data transmission by remote control. (October 2017) - Casciati, Sara; Vece, Michele
Highlights: Development of a reliable scheme for a real-time SHM managed in remote control. Adoption of a Kalman-filter-based data fusion to make a precise measurement of the displacements of civil structures and infrastructures. Discussion about the features of the wireless transceiver and the tasks of the satellite communication. Description of hardware implementation and software architectures. Validation of the wireless data acquisition system by laboratory tests. Detailed analysis of the satellite transmission for a specialty test-bed. Abstract: The real time estimation of the displacements of civil structures is quite sensitive to the availability of wired links between the sensors and the remote control room. Many kinds of wireless displacement sensors or indirect measurements of them have been proposed. However, most of them suffer of large time delays and accuracy issues. In this paper, the authors adopt a Kalman-filter-based data fusion to make a precise measurement of the displacements in for civil structures and infrastructures. The required accuracy can be reached exploiting the real-time satellite corrections provided by a single reference station and combining them with the acceleration signals coming from three axial accelerometers. A wireless communication transfers the information coming from the coupling of GNSS receivers and three axial accelerometers. The proposed system is validated by control mechanism and laboratory tests. The ultimate goal is a reliable scheme for a real-time structural health monitoring managed in remote control.